Thermal Esophageal Injury following Ingestion of Boiling Mushroom Water - Allison Prevost; Adam Talley; Emily Klepper; Elizabeth McDonough (Hindawi Limited, 2017)
Thermal esophageal and gastric damage from ingestion of hot liquids is poorly studied in pediatrics. Limited case reports exist in the literature. Many cases presented with chest pain, dysphagia, and odynophagia. Variable histologic findings were reported. No definitive management guidelines exist for such injuries. We provide a report of the acute assessment and management of an obvious thermal esophageal injury and contribute to what is known about this presentation. A 16-year-old male presented with odynophagia, dysphagia, and hematemesis following ingestion of "nearly boiling" mushroom water. Ondansetron, pantoprazole, ketorolac, maintenance intravenous fluids, and a clear liquid diet were started. At sixty hours after ingestion, an esophagogastroduodenoscopy (EGD) revealed blistering and edema of the soft palate and epiglottis, circumferential erythema of the entire esophagus with an exudate likely to be desquamated mucosa, and linear erythema of the body and fundus of the stomach. An EGD one month after ingestion showed no residual effects from the injury. The pantoprazole was weaned and restrictions to his diet were lifted. To better standardize care in these rare esophageal injuries, the development of a clinical care algorithm may be beneficial to provide clinicians with a guide for management based on outcomes of previously reported cases.